Understanding COVID-19: are children the key? - Deirdre Kelly; Alex Richter; Suz Warner; Zania Stamataki (BMJ Publishing Group, 2021)
The devastating impact of the COVID-19 pandemic on global health and economic stability is immeasurable. The situation is dynamic and fast-evolving, with the world facing new variants of concern which may have immune escape potential. With threatened treatment and preventative strategies at stake, and the prospect of reinfection prolonging the pandemic, it is more crucial than ever to understand the pathogenesis of SARS-CoV-2 infection, which intriguingly disproportionately affects adults and the elderly. Children infected with SARS-CoV-2 remain largely asymptomatic or undergo a transient mild illness. Understanding why children have a milder phenotype and a significant survival advantage may help identify modifiable risk factors in adults. Current evidence suggests adults with COVID-19 show variability in innate and adaptive immune responses, which result in uncontrolled proinflammatory cytokine production in some patients, leading to severe disease and mortality. Children with acute COVID-19 infection seldom progress to acute respiratory distress syndrome and are less likely to exhibit the cytokine storm which is so prominent in adults. Even with the Kawasaki-like illness, a hyperinflammation syndrome also known as paediatric multisystem inflammatory syndrome temporally associated with SARS-CoV-2, mortality is low. The key to successfully combating SARS-CoV-2 and future zoonotic pandemics may lie in understanding these critical differences and merits focused consideration and research. The impact of community transmission among asymptomatic children is unknown; sustained global decline in infection rates and control of the COVID-19 pandemic may not be achieved until vaccination of children occurs. In this review, we discuss the fundamental differences in the immune response between children and adults in the fight against SARS-CoV-2.